High rates of mercury biomagnification in fish from Amazonian floodplain-lake food webs - Nyholt, Kelsey; Jardine, Timothy D.; Villamarín, Francisco; Jacobi, Cristina M. [UNESP]; Hawes, Joseph E.; Campos-Silva, João V.; Srayko, Stephen; Magnusson, William E. (Elsevier, 2022)
Despite a global phase out of some point sources, mercury (Hg) remains elevated in aquatic food webs, posing health risks for fish-eating consumers. Many tropical regions have fast growing organisms, potentially short food chains, and few industrial point sources, suggesting low Hg baselines and low rates of trophic magnification with limited risk to people. Nevertheless, insufficient work on food-web Hg has been undertaken in the tropics and fish consumption is high in some regions. We studied Hg concentrations in fishes from floodplain lakes of the Juruá River, Amazonas, Brazil with three objectives: 1) determine rates of Hg trophic magnification, 2) assess whether Hg concentrations are high enough to impact humans eating fish, and 3) determine whether there are seasonal differences in fish Hg concentrations. A total of 377 fish-muscle samples were collected from 12 floodplain lakes during the low-water (September 2018) and falling-water (June 2019) seasons and analysed for total Hg and stable nitrogen (N) isotopes. The average trophic magnification factor (increase per trophic level) was 10.1 in the low-water season and 5.4 in the falling-water season, both well above the global average for freshwaters. This high rate of trophic magnification, coupled with higher-than-expected Hg concentrations in herbivorous species, led to high concentrations (up to 17.6 ng/g dry weight) in predatory pirarucu and piranha. Nearly 70% of all samples had Hg concentrations above the recommended human-consumption guidelines. Average concentrations were 42% higher in the low-water season than the falling-water season, but differences varied by species. Since Hg concentrations are higher than expected and fish consumption in this region is high, future research should focus on Hg exposure for human populations here and in other tropical-rainforest regions, even in the absence of local point sources of Hg.
Keywords: Arapaima; Falling-water season; Low-water season; Methylmercury; Subsistence fishing; Trophic magnification